No-code video game development using Unity and PlayMaker - Kelley, Michael (CRC Press, Taylor & Francis Group, 2016)
In the past, not being able to program meant not being able to make video games. Now if you can draw a flow-chart you can use powerful State Machine technology to create your dream game! Whether you want to learn the basics of programming or bypass coding altogether, No-Code Video Game Development using Unity and Playmaker makes it as easy as 1, 2, 3. The book's DLC comes with Unity Packages, Playmaker Templates, Character Models, Animations, Materials, and more. You'll also learn game design documentation and theory, Mecanim, Particle Systems, and UI. By the time you're done you'll have gained the skills needed to create your own dream game, all without writing any code!